(untitled) (CIPEEX, 2025)
Financial technology companies, known as fintechs, have played a crucial role in modernizing the Brazilian financial system in the 21st century. These start-ups have emerged with the aim of filling gaps in the traditional banking system, offering financial services in a differentiated and accessible way. Several factors have driven the accelerated growth of fintechs in Brazil. Increased investment in technology by traditional banks, greater competitiveness in the sector with the entry of new players, changes in consumer behavior in relation to financial services and new regulations have made it possible for these companies to act more dynamically and flexibly. Fintechs have had a positive impact on the Brazilian financial system, increasing its efficiency, competitiveness and financial inclusion. They have facilitated access to financial services, especially for the low-income population, through innovation, reduced bureaucracy and more affordable costs. Although there are several studies on the impact of fintechs, many focus on specific aspects, such as the adoption of technologies or the regulation of the sector. There is a lack of research that comprehensively analyzes the factors that influence the impact of these companies on the financial system as a whole. Therefore, this study aimed to analyze the main factors that determine the impact of fintechs on the Brazilian financial system. Using a literature review of articles published in databases such as Web of Science, Scopus and SciELO, we included studies published in Portuguese or English, which assessed the impact of fintechs on the financial system, with free access and full availability, between 2020 and 2024. The search used three blocks of keywords related to the terms "fintechs", "financial system" and "Brazil". After removing duplicate articles, opinion pieces, comments and case reports, the final analysis consisted of 10 full articles. The analysis revealed that the main factors driving the growth of fintechs in Brazil were increased investment in technology by traditional banks, greater competitiveness in the sector with new entrants, changes in consumer behavior and new regulations. As for the positive impacts of fintechs, they were identified as increasing the efficiency and competitiveness of the sector, facilitating access to financial services, especially for the low-income population, and promoting innovation and reducing bureaucracy in the services offered. In conclusion, fintechs have played a fundamental role in transforming the Brazilian financial system, driven by various factors and generating positive impacts such as greater efficiency, competitiveness and financial inclusion. However, the scarcity of comprehensive research into the factors that influence this impact highlights the need for more studies in this constantly evolving area.